Managing the Revolution in Military Affairs
XXI, 273 p.
Keywords: The collapse of the Soviet Union and the end of the Cold War was the catalyst for profound changes in the global security and defence management environment, including: alterations in the size, structure and configuration of the Armed Forces; emergence of asymmetrical warfare; recognition of the strategic significance of military infosphere, embracing all dimensions of the 'virtual' and 'vertical' battlespace; emphasis on coalition warfare and defence-industrial cooperation; and reform of the financial, procurement and logistical systems. The contributors to this book evaluate these environmental changes within a defence management context.